INDONESIAN EFL STUDENTS’ PERSPECTIVES TOWARDS LEARNING MANAGEMENT SYSTEM SOFTWARE - Emiliana Putri; Fatimah Mulya Sari (fsip.teknokrat.ac.id, 2020)
The use of strategy takes an important role in language learning. The use of Learning Management System software (LMSs) in the EFL classroom enables the students to get their target language. LMSs has a feature that can enhance communication between student to student and between lecturer and students. This study generally explores students’ perspectives toward the use of LMSs as a language learning strategy. This qualitative research was conducted in Universities in Lampung Province, Indonesia. The subjects were 33 undergraduate students in the English Education study program, Faculty of Arts and Education. The data used were questionnaires and interviews. The findings show that the participants give positive feedback toward their experiences in using LMSs. By using LMSs, admitted that LMSs was given improvement to their speaking, reading, listening, and writing skill. However, some students revealed that there were some technical problems founds when they use LMSs, such as bad gateway connection. Nevertheless, learning a language using LMSs as the strategy helps the students to have self-learning experiences.